Kurikulum Merdeka dan Implementasinya terhadap Perencanaan Pembelajaran Matematika di SMK Negeri 6 Padang - Linda Amalia; Nita Putri Utami (Lembag, 2025)
This study aims to analyze the implementation of the Independent Curriculum in mathematics learning planning at SMK Negeri 6 Padang. The Independent Curriculum provides flexibility to teachers in designing contextual, student-centered, and character-oriented learning through the Pancasila Student Profile. This study uses a qualitative method with data collection techniques in the form of observation, interviews, and documentation. The results of the study indicate that SMK Negeri 6 Padang has implemented various important components in learning planning, such as the School Operational Curriculum (KOS), Academic Calendar, Effective Week Details, Annual Program (Prota), Semester Program (Promes), Learning Achievements (CP), Learning Objectives (TP), Learning Objective Achievement Criteria (KKTP), and Learning Objective Flow (ATP). However, the implementation of the Independent Curriculum still faces challenges, especially in the integration of the Pancasila Student Profile Strengthening Project (P5) and the application of differentiated learning. Thus it can be concluded that the Learning planning is very effective, namely 82.25%. Therefore, further training is needed to improve the quality of learning planning based on the Independent Curriculum. This study concludes that although mathematics learning planning has referred to the principles of the Independent Curriculum, ongoing training and systematic support are still needed to optimize the implementation of the curriculum in vocational schools.